Universal Call to Holiness and «Special Vocations». The Dilemma of Their Conceptualisation - Rojas, Hernán (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
The problem of an exceptionalist understanding of «vocation» highlights a complex dilemma about the relation between the universal call to holiness, enunciated by the last ecumenical Council, and the so-called «special vocations». It is postulated that there are two alternatives: (i) some in the Church are called to a «special vocation» (e. g. ordained ministry, religious life) based on the universal call to holiness which they share with all Christians, or (ii) the universal call to holiness only exists in concrete form as a «special vocation» which each person receives from God. While both options have advantages and difficulties of theological plausibility and pastoral convenience, the preference for the second alternative is justified.
Keywords: abuse; ecclesiology; Second Vatican Council; religious life; ordained ministry